Acariases - Kyle, Hernon Curtis (My University, 1903)
Introduction: The term acariases is applied to every disease caused by Acarina. The acarina form a separate order in the class Arachnida. Some of the members of this order are commonly known as mites and ticks. The abdomen of the acarina is unsegmented and fused with the thorax, giving the entire body a more or less sack appearance. In many the body is marked with transverse lines which appear like the divisions between minute segments. The majority of the acarina are very small, but some, as certain ticks, are of considerable size. All families of this order, except one, bring forth their young from eggs. The sexes are separate in all the Acarina; however, there is a smaller number of male than females. The males also differ from the females in being smaller and in certain details of conformation. They often have different habits of life. Neumann divides this order into ten families, five of which are of pathological importance. Their names are as follows: Ixodiae, Gamasidae, Trombidae, Sarcopridae, and Demodecidae. All of these have representatives on domestic mammals, and all are found on birds except the Demodecidae. The members of the first three families and certain individuals of the family Sarcoptidae merely live on the epidermic scales, and the remains of hairs and feathers or prick the skin in order to suck the blood. This action on the part of the parasite does not cause disturbance beyond the points of attack. However, the remaining individuals of the family Sarcoptidae and all the members of the family Demodecidae usually cause a very serious disease known aspsora or scabies. This serious disturbance is the result, not only of numerous bites but of the venom implanted, of the gallories they excavate, and of the deep situation in which they locate themselves. These two groups of parasites are called Non-Psoric and Psoric respectively.
Citation: Kyle, Hernon Curtis. Acariases. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Acariases; Acarina; Mites; Ticks; Disease; Microbiology; Arachnida; Scabies; Theses